2003
DOI: 10.1021/jf026234e
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on the Stability of Folic Acid and 5-Methyltetrahydrofolic Acid Degradation during Thermal Treatment in Combination with High Hydrostatic Pressure

Abstract: Stability of folic acid and 5-methyltetrahydrofolic acid in phosphate buffer (0.2 M; pH 7) toward thermal (above 65 degrees C) and combined high pressure (up to 800 MPa)/thermal (20 up to 65 degrees C) treatments was studied on a kinetic basis. Residual folate concentration after thermal and high pressure/thermal treatments was measured using reverse phase liquid chromatography. The degradation of both folates followed first-order reaction kinetics. At ambient pressure, the estimated Arrhenius activation energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 22 publications
11
41
0
Order By: Relevance
“…An example from the work by Nguyen et al [41] on the PATP degradation of 5-methyltetrahydrofolic acid (10 lg/ml) in phosphate buffer (0.2 M, pH 7) is shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example from the work by Nguyen et al [41] on the PATP degradation of 5-methyltetrahydrofolic acid (10 lg/ml) in phosphate buffer (0.2 M, pH 7) is shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 99%
“…In the pressure range of commercial processing . Adapted from Nguyen et al [41] interest (*500-700 MPa), an isothermal pressure increase of *200 MPa changes the first-order rate constant from 0.0075 to 0.115 min -1 while an isobaric temperature increase of only *7°C achieves the same effect. This is an excellent graphic means to illustrate the temperature and pressure dependence of PATP degradation of food quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fruit and vegetables, [6S]-5-methyltetrahydrofolate ([6S]-5-CH 3 PteH 4 Glu) is the predominant natural folate form, whereas PteGlu does not naturally occur in foods but is used for fortification. It is well established that [6S]-5-CH 3 PteH 4 Glu is unstable during thermal processing (Nguyen et al, 2003 and that addition of antioxidants results in a stabilization of the natural vitamin , Oey et al, 2006. It has previously been shown that in the presence of reducing sugars (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature of folate oxidation at 0.1MPa was shifted to lower temperatures when applying pressure (>50MPa) (because of negative activation volume). As compared to conventional thermal processing, the folate stability could also be affected during HP because oxidation reaction was enhanced (Nguyen et al 2003(Nguyen et al , 2006Indrawati et al 2004Indrawati et al , 2005, . In addition, validation studies in food matrices i.e.…”
Section: Resultsmentioning
confidence: 99%